Perception of Professional Practice in Students and University Teachers of Physical Education - Vásquez, Sara Agudelo; Monsalve, Mary Elena Ocampo; Castaño, Juan Paulo Marín (Journal of Posthumanism, 2025)
The study focused on professional practice, which can be understood as the process in which students apply theoretical knowledge in real contexts, contributing to the development of skills and abilities necessary to apply in their work. The objective was to identify the perception of the actors involved in the professional practice of the Bachelor’s Degree in Physical Education, Recreation and Sports of a university institution in Medellin-Colombia. Methodologically, a qualitative approach was used, based on case analysis. Nineteen students and 11 practice advisors participated. Data collection was carried out through semi-structured interviews and discussion groups, the information was analyzed through ATLAS.ti v. 22.2 software. The results show that for the students the components related to the practice process, accompaniment and academic component are fundamental, while for the advisors, the curricular structure, administrative conditions, attributes of the advisors, interns and practice center are central components. It is concluded that the pedagogical practice includes three factors, namely, relationship between theory and practice, roles of the actors and opportunities for improvement.